Building construction materials and techniques - Raj, P. Purushothama (Always learning., 2017)
Building Construction Materials and Techniques follows a unique approach to the subject by including both materials and construction techniques in a combined text as per the latest trends in university curriculums. It also caters to the needs of the universities where these subjects are offered across two semesters as well. Of the 32 chapters in this book, 13 are dedicated to building construction materials while the remaining 19 focus on conventional as well as modern techniques in construction. The chapters are supplemented by a plethora of self-explanatory illustrations for easy comprehension. Relevant references to IS codes and standards make this text ideal for extended learning.